Angiotensin II Type 1 Receptor (AT1R) Changes in Animal Model of Chronic Kidney Disease: Evaluation and Pharmacotherapy - Ismail, Basma (Université d'Ottawa / University of Ottawa, 2016)
Cardiovascular complications represent the leading cause of death in chronic kidney disease (CKD) patients. Significant renal mass reduction induced by 5/6 subtotal nephrectomy (Nx) animal model leads to a chain of events that culminates in hypertension and CKD. The renin angiotensin (Ang) system (RAS) is known to be dysregulated, specifically Ang type 1 receptor (AT1R) plays a major role in development and progression of the disease. However, conflicting results have been reported on intrarenal AT1R levels, and the impact of antihypertensive drugs on RAS signaling is divergent. We hypothesize that PET imaging will be able to quantify kidney AT1R expression reliably in healthy and disease states. The broad objectives of this research project were: (i) to develop a positron emission tomography (PET) probe capable of detecting changes in the AT1R binding in the kidney; (ii) to elucidate the nature/temporal role of renal AT1R in Nx rat model of CKD; and (iii) to explore the predictive value of non-invasive PET imaging of AT1R to guide the use of antihypertensive therapy in preventing the progression of the disease. The novel selective AT1R PET radioligand [18F]FPyKYNE-losartan was successfully used with PET in detecting renal AT1Rs at early and late stages of the CKD. The PET results correlated well with in vitro [125I]-[Sar1, Ile8]Ang II autoradiography. Over the time-course of the study (10-20 weeks), the Nx rats exhibited renal impairment, proteinuria and sustained hypertension. Echocardiography indicated the development of cardiac hypertrophy most likely secondary to the hyperdynamic circulation. These abnormalities were associated with increasing plasma and kidney levels of Ang II, and compensatory downregulation of renal AT1Rs. ACEI enalapril attenuated renal impairment, hypertension and prevented progression of cardiac hypertrophy in Nx rats. This was successfully accomplished through reduction of systemic and kidney Ang II, and consequent normalization of renal AT1R as measured by PET (and autoradiography). The non-dihydropyridine CCB diltiazem also reduced blood pressure but did not normalize renal AT1R expression. Diltiazem induced elevation in Ang II levels in plasma, kidney and heart, associated with exacerbation of renal and cardiac dysfunction, and no change in AT1R renal expression. This outcome adds value to the use of [18F]FPyKYNE-losartan PET for determination of receptor abnormalities with progression of the disease and monitoring of therapy.
Keywords: Angiotensin type 1 receptor; PET imaging; Chronic Kidney Disease; Antihypertensives